EFFICIENCY COOPERATION AND BLOCKING SMALL-VOLUME CATTLEBREEDING BUILDINGS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The method of evaluating the effectiveness of implementation of previous versions space-planning and design solutions to semi-detached buildings, determining the annual economic impact of introduction of semi-detached buildings. Keywords:cattle-breeding small-volume cooperative building, economiceffectiveness of blocking.